Mycobacterium bovis Δmce2 double deletion mutant protects cattle against challenge with virulent M. bovis - Blanco, Federico Carlos (2013)
A Mycobacterium bovis strain deleted in mce2A and mce2B genes (M. bovis Δmce2) was tested as an experimental vaccine in cattle challenged with a virulent M. bovis strain. Three-and-a-half-month old calves (n = 5 to 6 per group) were vaccinated and challenged with a virulent strain of M. bovis by the intratracheal route 9 weeks after vaccination. A non-vaccinated group and a group vaccinated with BCG were included as controls. Blood samples were collected to measure IFN-γ by an interferon-gamma release assay (IGRA), cytometry and cytokine responses of bovine purified protein derivative (PPD) restimulated peripheral blood mononuclear cells (PBMCs). The IGRA test showed IFN-γ values similar to pre-vaccination except for the animals vaccinated with M. bovis Δmce2, where a significant increase was observed at 30 days post-vaccination. The expression of IL-2R on CD4(+) cells in response to PPD from the animals vaccinated with Δmce2 increased at 15 days post-vaccination compared to cells from non-vaccinated group. Vaccination of cattle with M. bovis Δmce2 induced the highest (P < 0.05) expression of IFN-γ and IL-17 mRNA upon PPD stimulation of PBMCs compared to vaccination with BCG or that for the non-vaccinated group. There was a weak positive correlation between the production of these proinflammatory cytokines post-vaccination and reduced pathology scores post-challenge. The animals were euthanized and necropsied 100 days after challenge. The group vaccinated with M. bovis Δmce2 displayed a significantly lower histopathological score for lesions in lungs and pulmonary lymph nodes than for the other groups (P < 0.05). A marked positive reaction to tuberculin intradermal test was observed post-vaccination in animals vaccinated with M. bovis Δmce2 compared to those vaccinated with BCG or the non-vaccinated group. In contrast, after challenge, non-vaccinated animals had greater skin test responses than the vaccinated animals. In summary, M. bovis Δmce2 is a promising vaccine candidate to control M. bovis pathogenesis in cattle.